Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 5 - Section 5.4 - Multiplication of Monomials - Exercise - Page 224: 50



Work Step by Step

Since $a=2$ and $b=-3$, we have $$(3a)(-5b^2)=(3(-5)) (ab^2)=-15 (2)(-3)^2\\ =-30(9)=-270 .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.